PENGARUH CURRENT RATIO DAN QUICK RATIO TERHADAP PERUBAHAN LABA PADA PT. AKASHA WIRA INTERNASIONAL TBK - Anti Febi Insan; Ita Purnama (Jurnal Ilmiah Manajemen & Bisnis, 2021)
This study aims to determine the effect of liquidity ratios on changes in earnings at PT Akasha Wira Internasional Tbk listed on the Indonesian stock exchange (BEI). In this study, the company's liquidity ratio is measured by the Curren ratio and the Quick Ratio. The population in this study is the company PT. Akasha Wira Internasional Tbk which was listed on the Indonesia Stock Exchange during the 2006-2019 period. The sample of this study was used 10 years starting from 2010-2019 taken using purposive sampling method. data analysis used to test the hypothesis is to use multiple linear regression analysis techniques. From the research results, it was found that the results of the t test partially Current Ratio had no effect on changes in earnings as evidenced by a significant value of 0.678> 0.05, while the significant value of the Quick Ratio was 0.222> 0.05. This proves that the current ratio and quick ratio have no significant effect on changes in earnings. it can be concluded that the current ratio and quick ratio simultaneously do not have a significant effect on changes in earnings. The results of this study are in line with Gunawan and Wahyuni ??(2013). Keywords: Current Ratio, Quick Ratio, Profit Changes